A raspberry-shaped biodegradable porous microsphere with high mesoporosity and its preparation method and application

By introducing the mineralization and calcining steps of dextran microsphere templates in the preparation process of calcium hydroxyphosphate microspheres, raspberry-like degradable porous microspheres with high mesoporosis were prepared, which solved the problems of sharp microsphere structure, poor histocompatibility and lack of porous structure in the prior art, and achieved better histocompatibility and drug release efficiency.

CN119349524BActive Publication Date: 2025-04-25SHANGHAI MOYANG BIOTECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411883979.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-25
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, the microstructure of calcium hydroxyphosphate microspheres is relatively sharp, has relatively poor histocompatibility, and lacks a porous structure, which may trigger an inflammatory response after in vivo injection, which is not conducive to the regulation of drug load and degradation time.

Method used

By mineralizing the dextran microsphere template, a mineralized dextran microsphere template was obtained, and the dextran template was removed during the calcination process to prepare a raspberry-like degradable porous microsphere with high mesoporosis. The microspheres have a rough surface, a nano-scale pore structure and a porous structure, and can self-assemble to form spherical or irregular spherical microspheres.

Benefits of technology

It improves the histocompatibility of microspheres, reduces the probability of inflammatory reactions, and regulates the degradation rate and drug release efficiency of microspheres through porous structures. It is suitable for drug sustained-release carriers and tissue engineering stents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349524B_ABST
    Figure CN119349524B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, and discloses a raspberry-shaped degradable porous microsphere with high mesoporosity, a preparation method and an application thereof. The raspberry-shaped degradable porous microsphere with high mesoporosity is a nano-scale to micron-scale microsphere with a rough surface formed by self-assembly of nano-scale calcium hydroxyphosphate particles driven by thermodynamic behavior of reduced excess surface free energy. The raspberry-shaped degradable porous microsphere with high mesoporosity has a rough surface and a spherical morphology, as well as increased surface roughness and specific surface area, which are conducive to cell attachment, proliferation and adsorption of drug molecules. The spherical structure improves the mechanical microenvironment when in contact with surrounding tissues, and reduces the probability of inflammatory reactions. The porous structure increases the contact area with body fluids, regulates the degradation rate and the release efficiency of calcium ions, promotes the repair of skin barriers, and is conducive to loading drugs and stem cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a raspberry-shaped degradable porous microsphere with high mesoporosity, and a preparation method and application thereof. Background Art

[0002] Hydroxyapatite (HAp) is one of the most common forms of calcium phosphate, with a chemical formula of Ca 10 (PO4)6(OH)2 is the main inorganic mineral component of human bones and teeth. Hydroxycalcium phosphate is also widely present in nature, such as the bones of vertebrates and the shells of mollusks. Hydroxycalcium phosphate has good biocompatibility and bioactivity. As an inorganic bone substitute material, it has been widely used in the medical field and has shown extremely high application value in orthopedic surgery, maxillofacial surgery and drug controlled release. However, since the crystal form of hydroxycalcium phosphate belongs to the hexagonal system, P63 / m space group, and the crystallographic parameters are a = 9.418 Å, c = 6.881 Å, β = 120°, the smallest structural unit of hydroxycalcium phosphate prepared by traditional methods such as hydrothermal method is usually needle-shaped, which is easy to stimulate the surrounding tissues to produce inflammatory reactions after implantation in the body.

[0003] The preparation of calcium hydroxyphosphate into microspheres can improve the mechanical microenvironment when it contacts the surrounding tissues and reduce the probability of inflammatory response; the porous structure can increase the contact area between calcium hydroxyphosphate and body fluids after injection into the body, regulate its degradation rate to a certain extent, and facilitate the loading of drugs and stem cells. At present, the preparation methods of microspheres include hydrothermal method, spray drying method, sol-gel method, template method, etc.

[0004] For example, a Chinese patent (patent application number 202210911941.5) discloses a hydrothermal preparation method for porous microsphere materials, but its microstructure is clusters of needle-shaped and lamellar hydroxyapatite calcium phosphate, which may produce a large inflammatory response after injection. A Chinese patent (patent application number 202210364112.X) discloses a spray-drying preparation method for hydroxyapatite microspheres, but it does not have a porous structure, which is not conducive to loading drugs and regulating degradation time. A Chinese patent (patent application number 202310547230.9) discloses a template preparation method for injectable high-purity medical hydroxyapatite microspheres, which also does not have a porous structure.

[0005] Therefore, there is an urgent need for a raspberry-shaped biodegradable porous microsphere with high mesoporosity and a preparation method and application thereof to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a raspberry-shaped biodegradable porous microsphere with high mesoporosity and a preparation method and application thereof, thereby overcoming the defects of the microsphere in the prior art, such as relatively sharp microstructure, relatively poor tissue compatibility, and lack of porous structure.

[0007] The scheme of the present invention is:

[0008] A raspberry-shaped degradable porous microsphere with high mesoporosity. The raspberry-shaped degradable porous microsphere with high mesoporosity is self-assembled by nanoscale calcium hydroxyphosphate particles driven by the thermodynamic behavior of reducing excess surface free energy to form nanoscale to micrometer-sized microspheres with rough surfaces. The raspberry-shaped degradable porous microsphere with high mesoporosity is spherical or irregular in shape, and has a nanoscale pore structure, wherein the pore structure has one or a combination of cross-linked holes, through holes and blind holes.

[0009] As a preferred technical solution, the surface roughness of the microsphere is 5 to 150 nm; the particle size range of the microsphere is 300 nm to 150 μm; the average pore size of the microsphere is 0.1 nm to 150 nm; the porosity of the microsphere is 50% to 95%; the specific surface area of ​​the microsphere is 30 to 200 m 2 / g.

[0010] As a preferred technical solution, the surface roughness of the microspheres is 50-90 nm; the particle size range of the microspheres is 600 nm-75 μm; the pore size range of the microspheres is 2-50 nm; the porosity of the microspheres is 65%-80%; the specific surface area of ​​the microspheres is 60-150 m 2 / g. The particle size range of 600 nm to 75 μm can minimize the body's foreign body reaction to the raspberry-shaped degradable porous microspheres with high mesoporosity; for the pore size, porosity and specific surface area of ​​the raspberry-shaped degradable porous microspheres with high mesoporosity, there is an interactive relationship between the three parameters. In the range of pore size of 2 to 50 nm, porosity of 65% to 85%, and specific surface area of ​​60 to 100 m2 / g, an optimal balance can be achieved between the degradation time of calcium hydroxyphosphate, calcium ion release rate and drug release rate within this range. The surface roughness of 50 to 90 nm is conducive to the spreading of cells on the surface of the microspheres and enhances tissue compatibility.

[0011] The present invention also discloses a method for preparing raspberry-shaped degradable porous microspheres with high mesoporosity, comprising the following steps:

[0012] The dextran microsphere template is subjected to mineralization treatment to obtain a mineralized dextran microsphere template; and the dextran microsphere template is calcined to prepare raspberry-shaped degradable porous microspheres with high mesoporosity.

[0013] As a preferred technical solution, the preparation method of the dextran microsphere template is:

[0014] S1, adding a dextran solution having a concentration of 10-50% W / V to an alkaline solution, mixing well, to prepare an aqueous phase;

[0015] S2, adding the aqueous phase to the organic phase, mixing and pre-emulsifying to obtain an emulsion, wherein the organic phase is n-octane containing a surfactant;

[0016] S3, adding a crosslinking agent dropwise to the emulsion, reacting, filtering and separating the crosslinked product;

[0017] S4, washing the cross-linked product with n-octane and distilled water, then performing solvent exchange with a volatile solvent, and then drying in a vacuum to obtain a dextran microsphere template.

[0018] As a preferred technical solution, a dual centrifugal stirrer is used in S1 to mix the mixture completely;

[0019] The organic phase in S2 is injected into a three-necked glass reactor, which is equipped with a heat-insulating jacket, an overhead stirrer and a curved blade stirring paddle, and is connected to a syringe pump for adding reagents. A thermostatic bath is used to control the reaction temperature. After the aqueous phase is added to the reactor, it is stirred and pre-emulsified to form a W / O emulsion, and the surfactant is ensured to be completely adsorbed on the surface of the droplets;

[0020] In S3, the stirring speed is slowed down, a cross-linking agent is added dropwise to the reaction container using a syringe pump, and the reaction is stirred until the reaction is complete; the dextran microsphere template is separated from the reaction mixture by filtering with a filter membrane, and then washed twice with n-octane and distilled water in sequence; the dextran microsphere template is subjected to solvent exchange with a volatile solvent, and dried in a vacuum to completely remove the solvent;

[0021] The dried dextran microsphere template is placed in a chromatography column, and the chromatography column is washed alternately with a calcium salt aqueous solution and a phosphate aqueous solution, and after repeated multiple times, the dextran microsphere template is washed with purified water to obtain a mineralized dextran microsphere template;

[0022] The mineralized dextran microsphere template is placed in a muffle furnace for calcination to remove the dextran microsphere template, thereby preparing raspberry-shaped degradable porous microspheres with high mesoporosity.

[0023] As a preferred technical solution, the concentration of the dextran solution in the step S1 is 20-40% W / V; the weight average molecular weight Mw of the dextran is 40,000-60,000, and its polymer dispersibility index PDI is less than 2.0; the alkaline solution is a NaOH aqueous solution, and the concentration of the NaOH aqueous solution is 1-10 mol / L; the mixing in the step S1 is carried out by stirring, with a rotation speed of 2000-4000 rpm and stirring for 1-10 min.

[0024] As a preferred technical solution, the concentration of the NaOH aqueous solution is 2 to 4 mol / L.

[0025] The role of NaOH in the present invention is to increase the reaction activity, which can increase the reaction activity of dextran and the cross-linking agent, and can accelerate the cross-linking speed compared to when it is not added. The role of the cross-linking agent added dropwise by a syringe pump is to prevent the microspheres from agglomerating due to collision, and compared to directly adding all of it, it has the effect of obtaining microspheres with more uniform particle sizes.

[0026] As a preferred technical solution, in the step S2, the volume ratio of the aqueous phase to the organic phase is 1 to 5:1;

[0027] The content of the surfactant in the organic phase is 0.1% to 2% W / V;

[0028] The surfactant is at least one of polyethylene glycol (200) monolaurate, glycerol monolaurate, N, N-dimethylhexanamide, polyglycerol fatty acid ester, polyethylene glycol (200) dilaurate, diglycerol monolaurate, sorbitol monolaurate, nonylphenoxypolyethoxyethanol and Span 80; the mixing in step S2 is carried out by stirring at a speed of 1000-2000 rpm for 5-30 min;

[0029] In the step S3, the crosslinking agent is at least one of diisocyanate, glutaraldehyde, epichlorohydrin, epibromohydrin, ethylene glycol diglycidyl ether, and 1,4-butanediol diglycidyl ether;

[0030] The method of adding the crosslinking agent dropwise is to use a syringe pump to add the crosslinking agent dropwise at a rate of 1 to 10 mL / h;

[0031] The molar ratio of dextran to the cross-linking agent is 1: 0.5-40 kg / mol;

[0032] The reaction time is 12 to 48 hours; the reaction temperature is 20°C to 50°C; stirring is performed during the reaction at a speed of 200 to 800 rpm;

[0033] In the step S3, the filtration is carried out by vacuum filtration using a microporous filter membrane, and the pore size of the filter membrane is 0.22 μm to 0.45 μm;

[0034] In the step S4, the volatile solvent is at least one of ethanol and acetone.

[0035] The present invention can enhance the stability of the emulsified system by adding a surfactant, and can also adjust the size of the prepared dextran soft template particle size by the amount of surfactant added, thereby adjusting the particle size of the microspheres after mineralization; for example, when the amount of surfactant added is less than 0.5 (W / V%), the prepared soft template particle size is relatively large, which is not conducive to sintering to obtain relatively regular microspheres in the subsequent preparation of hydroxy calcium phosphate microspheres, and too large a particle size will affect the drug loading efficiency in the drug loading process.

[0036] The present invention can adjust the cross-linking density of the dextran template by adding a cross-linking agent, especially the addition of epichlorohydrin, so as to regulate the subsequent mineralization efficiency of the template; however, if the ratio of the cross-linking agent to the dextran is too high, the cross-linking density of the prepared dextran soft template is relatively high, which is not conducive to the growth of calcium hydroxyphosphate crystals in the subsequent alternating mineralization process, and the obtained microspheres have a relatively low particle size, which can cause a strong immune response in the fields of drug delivery, soft tissue implantation, etc.

[0037] As a preferred technical solution, in the step S2, the volume ratio of the aqueous phase to the organic phase is 1 to 2:1;

[0038] The surfactant is at least one of polyethylene glycol (200) monolaurate, polyethylene glycol (200) dilaurate, and Span 80;

[0039] The mixing is performed by using a stirrer at a rotation speed of 1000 to 1500 rpm for 10 to 20 min;

[0040] The cross-linking agent is epichlorohydrin;

[0041] The method of adding the crosslinking agent dropwise is to use a syringe pump to add the crosslinking agent dropwise at a rate of 2 to 8 mL / h;

[0042] The molar ratio of the dextran to the cross-linking agent is 1:1.2-32 kg / mol;

[0043] The reaction time is 16 to 24 h; the reaction temperature is 35° C. to 45° C.; and the stirring in the S3 reaction is performed using a stirrer at a rotation speed of 300 to 500 rpm for 10 to 20 min.

[0044] As a preferred technical solution, the mineralization treatment method is: the dextran microsphere template is alternately rinsed with a calcium salt aqueous solution and a phosphate aqueous solution for ≥ 2 times, and then rinsed with purified water.

[0045] As a preferred technical solution, the concentration of the phosphate aqueous solution is 0.1-2.0 mol / L; the flow rate of the phosphate aqueous solution during flushing is 10-100 mL / h; the phosphate aqueous solution is one of diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate and potassium dihydrogen phosphate aqueous solutions;

[0046] The concentration of the calcium salt aqueous solution is 0.1-2.0 mol / L; the flow rate of the calcium salt aqueous solution during flushing is 10-100 mL / h; the calcium salt aqueous solution is one of calcium chloride, calcium bromide, calcium nitrate and dicalcium phosphate.

[0047] As a preferred technical solution, the concentration of the phosphate aqueous solution is 0.3-0.5 mol / L; the phosphate aqueous solution is diammonium hydrogen phosphate solution;

[0048] The concentration of the calcium salt aqueous solution is 0.3-0.5 mol / L; the calcium salt aqueous solution is a calcium nitrate solution.

[0049] The role of calcium salt and phosphate flushing in bionic mineralization is to generate hydroxy calcium phosphate nanoparticles through alternating mineralization. Compared with the impregnation method, the advantage of alternating mineralization is that it can improve the mineralization efficiency while obtaining hydroxy calcium phosphate nanocrystals with more perfect structure.

[0050] As a preferred technical solution, the calcination temperature is 600-1200° C. and the calcination time is 2-24 h.

[0051] As a preferred technical solution, the calcination temperature ranges from 800 to 1000° C. and the calcination time is 15 to 18 hours.

[0052] As a preferred technical solution, the drying method is to dry in a vacuum oven at 80°C or above to constant weight; the drying time is 2h to 24h; further preferably, the drying method is to dry at a temperature of 90°C and a pressure of 1.0×10 -3 MPa in a vacuum oven to dry to constant weight.

[0053] The invention also discloses the use of raspberry-shaped degradable porous microspheres with high mesoporosity in drug sustained-release carriers or tissue engineering scaffolds.

[0054] As a preferred technical solution, raspberry-shaped biodegradable porous microspheres with high mesoporosity have good adsorption capacity and are used as adsorbents, thereby being applied in related fields of use.

[0055] Due to the use of a raspberry-shaped degradable porous microsphere with high mesoporosity and its preparation method and application, the raspberry-shaped degradable porous microsphere with high mesoporosity is self-assembled by nanoscale calcium hydroxyphosphate particles driven by the thermodynamic behavior of reducing excess surface free energy to form nanoscale to micron-sized microspheres with a rough surface; the morphology of the raspberry-shaped degradable porous microsphere with high mesoporosity is spherical or irregular spherical, and the raspberry-shaped degradable porous microsphere with high mesoporosity has a nanoscale pore structure, and the pore structure has one or a combination of cross-linked holes, through holes and blind holes.

[0056] Advantages of the present invention:

[0057] The raspberry-shaped biodegradable porous microspheres with high mesoporosity of the present invention have a rough surface and a high surface roughness, thereby providing more structural support points and bioactive sites, facilitating cell attachment and proliferation, and facilitating the adsorption of drug molecules; the spherical morphology can improve the mechanical microenvironment when it contacts the surrounding tissues, and reduce the probability of inflammatory response;

[0058] In addition, the specific surface area will also affect the degradation rate of the raspberry-shaped degradable porous microspheres with high mesoporosity; the raspberry-shaped degradable porous microspheres with high mesoporosity prepared by the present invention also have a porous structure, and the morphology, size and other parameters of the nanoscale calcium hydroxyphosphate particles can be adjusted through the process to obtain high mesoporosity raspberry-shaped degradable porous microspheres with different pore sizes, porosities and specific surface areas; the porous structure can increase the contact area between calcium hydroxyphosphate and body fluids after being injected into the body, thereby regulating its degradation rate to a certain extent, thereby affecting the release efficiency of calcium ions. Calcium ions are an important element for the proliferation and differentiation of skin basal layer cells. Regulating the calcium ion concentration helps repair the skin barrier and is also beneficial for loading drugs and stem cells.

[0059] The preparation method used in the present invention is simple, the production process has a high safety factor, the obtained porous microspheres have a stable structure and various parameters can be adjusted according to demand, and are suitable for industrialized scale-up production.

[0060] The present invention can enhance the stability of the emulsified system by adding a surfactant; the addition of a crosslinking agent, especially epichlorohydrin, can adjust the crosslinking density of the dextran template to regulate the subsequent mineralization efficiency of the template; the role of NaOH is to increase the reaction activity, and the crosslinking speed can be accelerated compared to when it is not added. The role of the crosslinking agent added dropwise by an injection pump is to prevent the microspheres from agglomerating due to collision, and compared to directly adding all of them, it has the effect of obtaining microspheres with more uniform particle sizes. The role of using calcium salts and phosphates for flushing in bionic mineralization is to alternately mineralize and generate hydroxy calcium phosphate nanoparticles. Compared with the immersion method, the advantage is that the mineralization efficiency can be improved while obtaining hydroxy calcium phosphate nanocrystals with a more perfect structure.

[0061] The present invention adopts cross-linked activated dextran microspheres as templates, which have the ability to strongly induce the mineralization and deposition of calcium hydroxyphosphate; compared with other preparation methods of calcium hydroxyphosphate, the biomimetic mineralization method is not only environmentally friendly, simple in process, low in cost, and can effectively regulate the morphology and microstructure of crystals, but also the prepared composite microspheres have strong bonding between calcium hydroxyphosphate and modified dextran microspheres, so the interface compatibility between the two phases is good, and the calcium hydroxyphosphate layer is not easy to fall off and can be dispersed evenly. The parameters of the morphology and size of the nanoscale calcium hydroxyphosphate particles prepared by the dextran template are adjusted by the process, so that raspberry-shaped degradable porous microspheres with high mesoporosity of different pore sizes, porosities and specific surface areas can be obtained during the sintering process, and the corresponding pore structure will affect its degradation rate, and the degradation rate will affect the release efficiency of calcium ions, and calcium ions are an important element for the proliferation and differentiation of skin basal layer cells, and the regulation of calcium ion concentration is helpful for the repair of skin barrier. In addition, since the porous structure has good adsorption capacity, raspberry-shaped biodegradable porous microspheres can also be used as tissue engineering scaffolds to load drugs and cells, and slowly release them to repair tissue damage in the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is a scanning electron microscope image of raspberry-shaped degradable porous microspheres with high mesoporosity prepared by using dextran microspheres as soft templates and calcining and de-templating the templates after alternating mineralization in Example 1 of the present invention;

[0063] Figure 2 This is a scanning electron microscope image of the surface morphology of the raspberry-shaped degradable porous microspheres with high mesoporosity prepared by using dextran microspheres as soft templates and calcining and de-templating the templates after alternating mineralization in Example 1 of the present invention;

[0064] Figure 3 The transmission electron microscope image of hydroxy calcium phosphate nanoparticles in Example 1 of the present invention is obtained by using dextran microspheres as soft templates and then using ultrasonic crushing to demold the template after alternate mineralization; wherein nanoscale hydroxy calcium phosphate particles enriched on the mineralized dextran microsphere template are shown, and the nanoscale hydroxy calcium phosphate particles will self-assemble to form raspberry-shaped degradable porous microspheres with high mesoporosity during the subsequent calcination and demolding process; the hydroxy calcium phosphate nanoparticles are spherical or irregular spherical particles with a particle size of 10 to 70 nm and an aspect ratio of 1 to 5;

[0065] Figure 4 This is a BET nitrogen adsorption-desorption curve of the raspberry-shaped degradable porous microspheres with high mesoporosity in Example 1 of the present invention. DETAILED DESCRIPTION

[0066] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0067] In the following examples and comparative examples, polyethylene glycol (200) monolaurate was purchased from Chengdu Dianchun Technology Co., Ltd. with a purity of 99%; dextran was purchased from Yishen Biotechnology (Shanghai) Co., Ltd. with a weight average molecular weight of Mw50,000, product number 61210ES, and a purity of 99%.

[0068] Embodiment 1:

[0069] The organic continuous phase consisted of 2.45 L of n-octane containing 1% W / V polyethylene glycol (200) monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0070] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0071] The stirring speed was set to 400 rpm, and 1.6 mol of epichlorohydrin with a molar ratio of 200 to dextran was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0072] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0073] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 22.3 μm, a porosity of 80.2%, an average pore size of 21.5 nm, and a specific surface area of ​​58.8 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 63 nm.

[0074] Embodiment 2:

[0075] The organic continuous phase consisted of 2.45 L of n-octane containing 1% W / V polyethylene glycol (200) monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0076] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified by stirring at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0077] The stirring speed was set to 400 rpm, and 2.4 mol of ethylene glycol diglycidyl ether was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0078] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0079] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 8 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 900 °C for 18 h to remove the dextran template to prepare a nanostructured product with an average particle size of 35.8 μm, a porosity of 86.7%, an average pore size of 35.0 nm, and a specific surface area of ​​77.4 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 78 nm.

[0080] Embodiment 3:

[0081] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V Span 80. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0082] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified by stirring at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0083] The stirring speed was set to 400 rpm, and 1.2 mol of ethylene glycol diglycidyl ether was added to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0084] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0085] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 27.4 μm, a porosity of 82.3%, an average pore size of 31.2 nm, and a specific surface area of ​​70.9 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 69 nm.

[0086] Embodiment 4:

[0087] The organic continuous phase consisted of 2.45 L of n-octane containing 1% W / V polyethylene glycol (200) dilaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0088] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0089] The stirring speed was set to 400 rpm, and 2.4 mol of epichlorohydrin was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0090] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0091] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 56.7 μm, a porosity of 90.1%, an average pore size of 43.0 nm, and a specific surface area of ​​85.8 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 107 nm.

[0092] Embodiment 5:

[0093] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V polyethylene glycol (200) dilaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0094] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0095] The stirring speed was set to 400 rpm, and 2.4 mol of epibromopropane was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0096] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0097] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 46.9 μm, a porosity of 93.7%, an average pore size of 77.5 nm, and a specific surface area of ​​91.2 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 134 nm.

[0098] Embodiment 6:

[0099] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V polyethylene glycol (200) dilaurate. The organic continuous phase was injected into a 4L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40°C using a thermostatic bath.

[0100] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 10 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0101] The stirring speed was set to 400 rpm, and 0.6 mol of epibromopropane was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0102] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0103] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 46.9 μm, a porosity of 93.7%, an average pore size of 38.1 nm, and a specific surface area of ​​96.2 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 72 nm.

[0104] Embodiment 7:

[0105] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V polyethylene glycol (200) dilaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0106] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0107] The stirring speed was set to 400 rpm, and 3.2 mol of epibromopropane was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0108] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0109] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 51.2 μm, a porosity of 94.8%, an average pore size of 114.5 nm, and a specific surface area of ​​133.1 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 145 nm.

[0110] Embodiment 8:

[0111] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V polyethylene glycol (200) dilaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0112] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified by stirring at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0113] The stirring speed was set to 400 rpm, and 1.6 mol of epibromopropane was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0114] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0115] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 39.9 μm, a porosity of 83.7%, an average pore size of 28.4 nm, and a specific surface area of ​​74.4 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 65 nm.

[0116] Embodiment 9:

[0117] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V sorbitan monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0118] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0119] The stirring speed was set to 400 rpm, and 3.2 mol of glutaraldehyde was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0120] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0121] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 75.5 μm, a porosity of 85.2%, an average pore size of 31.1 nm, and a specific surface area of ​​81.0 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 71 nm.

[0122] Embodiment 10:

[0123] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V sorbitan monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0124] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0125] The stirring speed was set to 400 rpm, and 1.6 mol of glutaraldehyde was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0126] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0127] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 26.0 μm, a porosity of 85.2%, an average pore size of 27.5 nm, and a specific surface area of ​​85.7 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 77 nm.

[0128] Embodiment 11:

[0129] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V sorbitan monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0130] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0131] The stirring speed was set to 400 rpm, and 3.2 mol of glutaraldehyde was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0132] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0133] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 26.0 μm, a porosity of 87.6%, an average pore size of 68.3 nm, and a specific surface area of ​​115.5 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 132 nm.

[0134] Embodiment 12:

[0135] The organic continuous phase consisted of 2.45 L of n-octane containing 1% W / V sorbitan monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0136] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0137] The stirring speed was set to 400 rpm, and 2.4 mol of epichlorohydrin was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0138] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0139] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 39.1 μm, a porosity of 81.0%, an average pore size of 24.4 nm, and a specific surface area of ​​62.4 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 65 nm.

[0140] Embodiment 13:

[0141] The organic continuous phase consisted of 2.45 L of n-octane containing 1% W / V sorbitan monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0142] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0143] The stirring speed was set to 400 rpm, and 1.2 mol of epichlorohydrin was added to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction.

[0144] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0145] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 25.6 μm, a porosity of 83.4%, an average pore size of 38.2 nm, and a specific surface area of ​​66.8 m 2 / g, and the surface roughness of the biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity is 72 nm.

[0146] Embodiment 14:

[0147] The organic continuous phase consisted of 2.45 L of n-octane containing 0.5% W / V sorbitan monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for the dropwise addition of reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0148] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 20% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified by stirring at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0149] The stirring speed was set to 400 rpm, and 1.2 mol of 1,4-butanediol diglycidyl ether was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0150] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0151] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 43.2 μm, a porosity of 79.8%, an average pore size of 11.5 nm, and a specific surface area of ​​52.7 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 45 nm.

[0152] Embodiment 15:

[0153] The organic continuous phase consisted of 2.45 L of n-octane containing 1% W / V N, N-dimethylhexanamide. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40°C using a thermostatic bath.

[0154] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0155] The stirring speed was set to 400 rpm, and 3.2 mol of 1,4-butanediol diglycidyl ether was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0156] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0157] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 74.5 μm, a porosity of 92.3%, an average pore size of 17.8 nm, and a specific surface area of ​​110.4 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 88 nm.

[0158] Embodiment 16:

[0159] The organic continuous phase consisted of 2.45 L of n-octane containing 0.05% W / V N, N-dimethylhexanamide. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0160] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 40% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0161] The stirring speed was set to 400 rpm, and 2.4 mol of 1,4-butanediol diglycidyl ether was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0162] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0163] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 57.10 μm, a porosity of 91.2%, an average pore size of 56.5 nm, and a specific surface area of ​​101.5 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 83 nm.

[0164] Embodiment 17:

[0165] The organic continuous phase consisted of 2.45 L of n-octane containing 2% W / V N, N-dimethylhexanamide. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40°C using a thermostatic bath.

[0166] The aqueous phase was prepared by adding 1 L of 2 mol / L NaOH solution to 2 L of 10% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0167] The stirring speed was set to 400 rpm, and 6.4 mol of 1,4-butanediol diglycidyl ether was added dropwise to the reaction vessel at a rate of 2 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0168] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0169] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 0.34 μm, a porosity of 94.1%, an average pore size of 142.0 nm, and a specific surface area of ​​189.7 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 149 nm.

[0170] Embodiment 18:

[0171] The organic continuous phase consisted of 2.45 L of n-octane containing 2% W / V N, N-dimethylhexanamide. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40°C using a thermostatic bath.

[0172] The aqueous phase was prepared by adding 1 L of 4 mol / L NaOH solution to 2 L of 80% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0173] The stirring speed was set to 400 rpm, and 1.2 mol of 1,4-butanediol diglycidyl ether was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0174] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0175] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 149.7 μm, a porosity of 52.2%, an average pore size of 2.1 nm, and a specific surface area of ​​39.1 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 6.4 nm.

[0176] Comparative Example 1:

[0177] Compared with Example 1, the organic continuous phase does not contain a surfactant, and other conditions are the same. During the synthesis reaction, dextran agglomerates and does not form microspheres, and cannot be used as a mineralization template for raspberry-shaped degradable porous microspheres with high mesoporosity.

[0178] Comparative Example 2:

[0179] Compared with Example 1, no crosslinking agent was added, and other conditions were the same. After stopping stirring and demulsification, the dextran was not completely crosslinked, and the solution was in a non-uniform gel state, which could not be used as a mineralization template for raspberry-shaped degradable porous microspheres with high mesoporosity.

[0180] Comparative Example 3:

[0181] Compared with Example 1, the aqueous phase does not contain sodium hydroxide, and other conditions are the same. After the synthesis reaction is completed, the dextran is a two-phase solution and cannot be used as a mineralization template for the raspberry-shaped degradable porous microspheres with high mesoporosity.

[0182] Comparative Example 4:

[0183] The organic continuous phase consisted of 2.45 L of n-octane containing 0.05% W / V polyethylene glycol (200) monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0184] The aqueous phase was prepared by adding 20 L of 0.1 mol / L NaOH solution to 8 L of 5% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0185] The stirring speed was set to 400 rpm, and 1.6 mol of epichlorohydrin was added to the reaction vessel at a rate of 4 mL / h using a syringe pump. The reaction was stirred for 18 h to ensure complete reaction. The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane, and then washed twice with n-octane and distilled water in sequence. The microspheres were solvent exchanged with acetone and / or ethanol and dried in a vacuum to completely remove the solvent.

[0186] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 10 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 1000°C for 15 h to remove the dextran template to prepare a nanostructured product with an average particle size of 0.07 μm, a porosity of 98.9%, an average pore size of 182.0 nm, and a specific surface area of ​​392.3 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 2 nm.

[0187] Comparative Example 5:

[0188] The organic continuous phase consisted of 2.45 L of n-octane containing 5% W / V polyethylene glycol (200) monolaurate. The organic continuous phase was injected into a 10 L three-necked glass reactor equipped with an insulation jacket, an overhead stirrer and a curved blade stirring paddle, and connected to a syringe pump for adding reagents. The reaction temperature was controlled at 40 °C using a thermostatic bath.

[0189] The aqueous phase was prepared by adding 0.4 L of 10 mol / L NaOH solution to 0.667 L of 60% W / V dextran solution, and then homogenizing at 3000 rpm for 5 min using a dual centrifugal stirrer until it was completely mixed. After the aqueous phase was added to the reactor, it was pre-emulsified by stirring at 1300 rpm for 15 min to form a W / O emulsion and ensure that the surfactant was completely adsorbed on the droplet surface.

[0190] The stirring speed was set to 400 rpm, and 2.4 mol of ethylene glycol diglycidyl ether was added dropwise to the reaction vessel at a rate of 4 mL / h using a syringe pump, and the reaction was stirred for 18 h to ensure complete reaction.

[0191] The microspheres were separated from the reaction mixture by filtration with a 0.22 μm filter membrane and then washed twice with n-octane and distilled water, respectively. The microspheres were solvent exchanged with acetone and / or ethanol and dried in vacuo to completely remove the solvent.

[0192] The dried microspheres were placed in a chromatography column, and the chromatography column was alternately washed with 0.5 mol / L calcium nitrate solution and 0.3 mol / L diammonium hydrogen phosphate solution at a flow rate of 60 mL / h. After repeating 8 times, the microspheres were washed with purified water and then placed in a muffle furnace and calcined at 900 °C for 18 h to remove the dextran template to prepare a microsphere with an average particle size of 350 μm, a porosity of 23.3%, an average pore size of 161.0 nm, and a specific surface area of ​​101.2 m 2 / g, biomimetic biomineralized raspberry-shaped biodegradable porous microspheres with high mesoporosity and surface roughness of 189 nm.

[0193] It can be seen from Comparative Examples 1 to 3 that when the dextran microsphere template of the present invention is prepared, if no surfactant, cross-linking agent or sodium hydroxide is added, it cannot be used as a mineralization template for raspberry-shaped degradable porous microspheres with high mesoporosity.

[0194] Table 1

[0195] serial number Dextran concentration / (W / V %) Dextran / (g) Sodium hydroxide concentration / M Sodium hydroxide / (mol) Surfactant concentration / (W / V %) Cross-linking agent / (mol) Particle size / μm Porosity / % Average pore size / nm Surface roughness / (nm) <![CDATA[Specific surface area / (m 2 / g)]]> Example 1 20 400 2 2 1 1.6 22.3 80.2 21.5 63 58.8 Example 2 20 400 4 4 1 2.4 35.8 86.7 35.0 78 77.4 Example 3 20 400 2 2 0.5 1.2 27.4 82.3 31.2 69 70.9 Example 4 40 800 4 4 1 2.4 56.7 90.1 43.0 107 85.8 Example 5 40 800 2 2 0.5 2.4 46.9 93.7 77.5 134 91.2 Example 6 20 400 4 4 1 0.6 34.6 82.9 38.1 72 96.2 Example 7 40 800 2 2 0.5 3.2 51.2 94.8 114.5 145 133.1 Example 8 20 400 4 4 0.5 1.6 39.9 83.7 28.4 65 74.4 Example 9 40 800 4 4 0.5 3.2 75.5 85.2 31.1 71 81.0 Example 10 20 400 2 2 0.5 1.6 26 87.6 27.5 77 85.7 Embodiment 11 40 800 2 2 1 3.2 37.9 94.2 68.3 132 115.5 Example 12 40 800 2 2 1 2.4 39.1 81 24.4 65 62.4 Example 13 20 400 2 2 1 1.2 25.6 83.4 38.2 72 66.8 Embodiment 14 20 400 4 4 0.5 1.2 43.2 79.8 11.5 45 52.7 Embodiment 15 40 800 4 4 1 3.2 74.5 92.3 17.8 88 110.4 Example 16 40 800 4 4 0.5 2.4 57.1 91.2 56.5 83 101.5 Embodiment 17 10 200 2 2 0.5 6.4 0.34 94.1 142.0 149 189.7 Embodiment 18 80 1600 4 4 2 1.2 149.7 52.2 2.1 6.4 39.1 Comparative Example 4 5 400 0.1 2 2 1.6 0.07 98.9 182 2 392.3 Comparative Example 5 60 400 10 4 0.05 2.4 350 23.3 161 189 101.2

[0196] Note: Average particle size in the table: tested by Malvern Mastersizer 3000 laser particle size analyzer; Porosity: tested by AutoPore IV 9510 high-performance fully automatic mercury intrusion instrument; Average pore size & specific surface area: tested by Micromeritics 3Flex fully automatic specific surface and porosity analyzer (BET); Surface roughness: tested by KEYENCE VK-X1000 laser microscope.

[0197] Load detection experiment:

[0198] Take 0.1 g of the raspberry-shaped degradable porous microspheres with high mesoporosity prepared in Examples 1 and 2 and Comparative Examples 4 and 5, soak them in 100 mL, 100 μg / L solution containing growth factors, take them out after soaking for 3 hours, measure the growth factor concentration in the solution after loading by ultraviolet spectrophotometry, and calculate the loading rate of the growth factor by comparing the absorbance of the original growth factor solution and the absorbance of the microspheres after adsorption of the loaded growth factor. The calculation method is as follows:

[0199] LE(%)=[1-(OD0-OD1) / OD0]×100%

[0200] LE is the growth factor loading rate, OD0 is the absorbance of the original solution of the growth factor, and OD1 is the absorbance of the microspheres after the growth factor is adsorbed and loaded; wherein the growth factor includes fibroblast growth factor and epidermal growth factor, and the specific data are as follows:

[0201] Table 2

[0202]

[0203] Table 1 shows the ranges of parameters such as raw material dosage and concentration of Examples 1 and 2 and Comparative Examples 4 and 5. Combined with the loading test experimental data in Table 2, it can be seen that the growth factor loading rates of Examples 1 and 2 are 48.7% and 45.2%, respectively, which are greater than 17.2% and 5.8% of Comparative Examples 4 and 5.

[0204] Therefore, the raspberry-shaped degradable porous microspheres with high mesoporosity of the present invention have the beneficial effect of high drug loading.

[0205] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing raspberry-shaped biodegradable porous microspheres with high mesoporosity, characterized in that: The following steps are involved: S1. Adding a 10-50% W / V dextran solution to an alkaline solution, mixing them evenly, to obtain an aqueous phase; the weight average molecular weight Mw of the dextran is 40,000-60,000, and its polymer dispersity index PDI is less than 2.0; the alkaline solution is a NaOH aqueous solution, and the concentration of the NaOH aqueous solution is 1-10 mol / L; S2, adding the aqueous phase to the organic phase, mixing and pre-emulsifying to obtain an emulsion, wherein the organic phase is n-octane containing a surfactant; the volume ratio of the aqueous phase to the organic phase is 1 to 5:1; and the content of the surfactant in the organic phase is 0.1% to 2% W / V; S3, adding a crosslinking agent to the emulsion, reacting, filtering and separating the crosslinked product; the method of adding the crosslinking agent is to use a syringe pump to add at a speed of 1-10 mL / h; the ratio of dextran to the crosslinking agent is 1:0.5-40 kg / mol; the reaction time is 12-48 h; the reaction temperature is 20°C-50°C; stirring is performed during the reaction at a speed of 200-800 rpm; the filtration in the S3 step is performed by vacuum filtration with a microporous membrane, and the pore size of the membrane is 0.22 μm-0.45 μm; S4, washing the cross-linked product with n-octane and distilled water, then performing solvent exchange with a volatile solvent, and then drying in a vacuum to obtain a dextran microsphere template; S5, mineralizing the dextran microsphere template to obtain a mineralized dextran microsphere template; calcining the dextran microsphere template to prepare a raspberry-shaped degradable porous microsphere with high mesoporosity.

2. The method for preparing a raspberry-shaped biodegradable porous microsphere with high mesoporosity according to claim 1, characterized in that: The concentration of the dextran solution in step S1 is 20-40% W / V; the mixing in step S1 is performed by stirring at a rotation speed of 2000-4000 rpm for 1-10 minutes.

3. The method for preparing a raspberry-shaped biodegradable porous microsphere with high mesoporosity according to claim 1, characterized in that: The surfactant is at least one of polyethylene glycol monolaurate, glycerol monolaurate, N,N-dimethylhexanamide, polyglycerol fatty acid ester, polyethylene glycol dilaurate, diglycerol monolaurate, sorbitol monolaurate, nonylphenoxypolyethoxyethanol and Span 80; the mixing in step S2 is carried out by stirring at a speed of 1000-2000 rpm for 5-30 minutes; In the step S3, the crosslinking agent is at least one of diisocyanate, glutaraldehyde, epichlorohydrin, epibromohydrin, ethylene glycol diglycidyl ether, and 1,4-butanediol diglycidyl ether; In the step S4, the volatile solvent is at least one of ethanol and acetone.

4. The method for preparing a raspberry-shaped biodegradable porous microsphere with high mesoporosity according to claim 1, characterized in that: The mineralization treatment is to alternately rinse the dextran microsphere template with a calcium salt aqueous solution and a phosphate aqueous solution for ≥2 times, and then rinse with purified water.

5. The method for preparing a raspberry-shaped biodegradable porous microsphere with high mesoporosity according to claim 4, characterized in that: The concentration of the phosphate aqueous solution is 0.1-2.0 mol / L; the flow rate of the phosphate aqueous solution during flushing is 10-100 mL / h; the phosphate aqueous solution is one of diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate and potassium dihydrogen phosphate aqueous solution; The concentration of the calcium salt aqueous solution is 0.1-2.0 mol / L; the flow rate of the calcium salt aqueous solution during flushing is 10-100 mL / h; the calcium salt aqueous solution is one of calcium chloride, calcium bromide, calcium nitrate and dicalcium phosphate.

6. The method for preparing a raspberry-shaped biodegradable porous microsphere with high mesoporosity according to claim 1, characterized in that: The calcination temperature is 600-1200° C. and the calcination time is 2-24 hours.

7. A raspberry-shaped biodegradable porous microsphere with high mesoporosity, characterized in that: The raspberry-shaped degradable porous microspheres with high mesoporosity are prepared by the preparation method of the raspberry-shaped degradable porous microspheres with high mesoporosity described in any one of claims 1 to 6. The morphology of the raspberry-shaped degradable porous microspheres with high mesoporosity is spherical or irregular, and the raspberry-shaped degradable porous microspheres with high mesoporosity have a nanoscale pore structure, and the pore structure has one or a combination of cross-linked holes, through holes and blind holes; the surface roughness of the microspheres is 5 to 150 nm; the particle size range of the microspheres is 300 nm to 150 μm; the average pore size of the microspheres is 0.1 nm to 150 nm; the porosity of the microspheres is 50% to 95%; and the specific surface area of ​​the microspheres is 30 to 200 m2 / g.

8. Use of the raspberry-shaped degradable porous microspheres with high mesoporosity prepared by the method for preparing raspberry-shaped degradable porous microspheres with high mesoporosity according to any one of claims 1 to 6 in drug sustained-release carriers or tissue engineering scaffolds.

Citation Information

Patent Citations

  • Hydroxyapatite microspheres and preparation method thereof

    CN114890398A

  • A porous hydroxyapatite microsphere material and its preparation method

    CN115108542B

  • Injectable high-purity medical hydroxyapatite microsphere and preparation method thereof

    CN116946993A

  • Microsphere composite hydrogel as well as preparation method and application thereof

    CN115947957A

  • Preparation method of controllable ordered mesoporous silica microspheres

    CN116282049A